2015
DOI: 10.1371/journal.pone.0143593
|View full text |Cite
|
Sign up to set email alerts
|

M2 Polarization of Human Macrophages Favors Survival of the Intracellular Pathogen Chlamydia pneumoniae

Abstract: Intracellular pathogens have developed various strategies to escape immunity to enable their survival in host cells, and many bacterial pathogens preferentially reside inside macrophages, using diverse mechanisms to penetrate their defenses and to exploit their high degree of metabolic diversity and plasticity. Here, we characterized the interactions of the intracellular pathogen Chlamydia pneumoniae with polarized human macrophages. Primary human monocytes were pre-differentiated with granulocyte macrophage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
89
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 43 publications
15
89
1
Order By: Relevance
“…This was consistent with previous studies on iPSDM with another cell lineage which concluded that iPSDMs are fully mature but can be differentiated into M2 or M1 polarized cells13. Thus these cells were considered M0 macrophages that, like M2 macrophages but not M1 macrophages, are permissive for Chlamydia growth78.…”
Section: Resultssupporting
confidence: 90%
“…This was consistent with previous studies on iPSDM with another cell lineage which concluded that iPSDMs are fully mature but can be differentiated into M2 or M1 polarized cells13. Thus these cells were considered M0 macrophages that, like M2 macrophages but not M1 macrophages, are permissive for Chlamydia growth78.…”
Section: Resultssupporting
confidence: 90%
“…29 In vitro , these two phenotypes can be polarizable with the addition of IFN-γ/LPS or IL-4/IL-10. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, M2 polarization of human macrophages was recently shown to favor also replication of Chlamydia pneumoniae (Buchacher et al, 2015). …”
Section: Metabolic Adaptations Of Iis Cells and The Ibpsmentioning
confidence: 99%